2010
DOI: 10.1038/nmat2859
|View full text |Cite
|
Sign up to set email alerts
|

Orally delivered thioketal nanoparticles loaded with TNF-α–siRNA target inflammation and inhibit gene expression in the intestines

Abstract: Gene silencing via orally delivered small interfering RNAs (siRNAs) represents a promising treatment strategy for numerous gastrointestinal (GI) diseases associated with chronic intestinal inflammation; however, the oral delivery of siRNA to inflamed isntestinal tissues remains a major challenge. Here, we present a delivery vehicle for siRNA, termed thioketal nanoparticles (TKNs), that can localize orally deliver siRNA to sites of intestinal inflammation, and thus inhibit gene expression in diseased intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
459
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 635 publications
(487 citation statements)
references
References 26 publications
2
459
3
6
Order By: Relevance
“…Poly(propylene sulfi de) [19][20][21][22] Selenium-containing polymers [26,28,29] [ 25,30] Telluriumcontaining polymers [35][36][37] Poly(thioketal) [38][39][40]46] [ [41][42][43][44][45]55] Phenylboronic acid/ ester containing polymers Poly(L-methionine) [49] Poly(L-proline) [53,54] Macromolecular Bioscience www.mbs-journal.de and SN38 resulted in enhanced proliferation inhibition of tumor cells via inducing cell apoptosis. In addition to drug carrier, the thioether-containing particles themselves can also show inherent therapeutic properties against oxidative stress.…”
Section: Chemical Structure and Oxidation Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(propylene sulfi de) [19][20][21][22] Selenium-containing polymers [26,28,29] [ 25,30] Telluriumcontaining polymers [35][36][37] Poly(thioketal) [38][39][40]46] [ [41][42][43][44][45]55] Phenylboronic acid/ ester containing polymers Poly(L-methionine) [49] Poly(L-proline) [53,54] Macromolecular Bioscience www.mbs-journal.de and SN38 resulted in enhanced proliferation inhibition of tumor cells via inducing cell apoptosis. In addition to drug carrier, the thioether-containing particles themselves can also show inherent therapeutic properties against oxidative stress.…”
Section: Chemical Structure and Oxidation Referencesmentioning
confidence: 99%
“…[ 38,39 ] Xia and co-workers developed a ROScleavable polymer for targeted gene delivery in cancer cells. [ 40 ] The unique physiological environments of intracellular space or tumor sites are usually used as specifi c biological triggers for smart drug delivery systems, such as weakly acidic pH value in tumor sites.…”
Section: Poly(thioketal)mentioning
confidence: 99%
“…Most of the current oral formulations for IBD therapy, which include pellets, capsules, and tablets, are based on pH-, pressure-, or bacteria-responsive mechanisms [17], and can only perform organ-level targeting. NPs, in contrast, have the potential to accumulate in inflamed colon tissues passively, and studies have shown that reactive oxygen species (ROS)-sensitive formulations can induce active targeted drug delivery at the tissue level [18]. For cell-level delivery of NPs, receptormediated drug delivery is a promising approach for achieving target specificity and avoiding nonspecific interactions.…”
Section: Oral Administrationmentioning
confidence: 99%
“…In pharmaceuticals, it has been applied to cure infection [2], cancer [3], allergy [4], diabetes [5] and inflammation [6].…”
Section: Introductionmentioning
confidence: 99%